REFLEKSI FILOSOFIS TERHADAP KONSEP SEJARAH FRANCIS FUKUYAMADARI BUKU THE END OF HISTORY AND THE LAST MAN - Wawaysadhya Wawaysadhya (PUSAT MPK UNIVERSITAS BRAWIJAYA, 2019)
This paper is analyzing the thought of Francis Fukuyama based on his book “The End of History and The Last Man”, for his contribution in philosophy of history, and the effected of the historical motion that occurred in Indonesia. Fukuyama explained that liberal democracy will have significant impact on the world social and technological development, which transforms human life into technology dependence. Now, Humans are